Ganoderma lucidum as a cosmeceutical: antiradical potential and inhibitory effect on hyperpigmentation and skin extracellular matrix degradation enzymes - Kozarski, Maja; Klaus, Anita; Jakovljević, Dragica; Todorović, Nina; Wan-Mohtar, Wan Abd Al Qadr Imad; Nikšić, Miomir (Archives of Biological Sciences, 2019)
Paper description: Ganoderma lucidum (Curtis) P. Karst is a source of bioactive molecules with various medical activities. The polysaccharide extracts of G. lucidum at different levels of purification protects skin from aging without cytotoxicity to HaCaT keratinocytes. Naturally-sourced inhibitors of collagenase, elastase and tyrosinase do not belong to polyphenolic extracts. Polysaccharide extracts are more efficient inhibitors of lipid peroxidation than additives commonly used in cosmeceutical formulations. The results of this study point to the need for evaluating polysaccharide extracts in cosmeceutical studies as multi-functional and non-toxic natural products. Abstract: Three different polysaccharide extracts of a wild European source of the mushroom Ganoderma lucidum were screened for their free radical-blocking potential, which could strengthen the skin’s barrier function, and provide a skin-lightening effect via potential inhibition of tyrosinase. The anti-collagenase and anti-elastase activities, which can help to restore skin elasticity and tensile strength, were also evaluated for the three extracts. Carbohydrates were the most abundant components of the extracts, followed by smaller quantities of proteins, phenols and flavonoids. The glucan fraction represented between 48% and 61% of carbohydrate content in all three extracts. None of the analyzed extracts showed overt toxicity to spontaneously-transformed immortal human keratinocytes (HaCaT) at concentrations up to 2 mg/mL, and displayed superior scavenging ability on 2,2′-azinobis(3-ethylbenzothiazoline-6-sulfonic acid (ABTS) and 1,1-diphenyl-2-picrylhydrazyl (DPPH) radicals. The hot water crude polysaccharide extract (HWCP) and partially purified fraction (HWPP) were found to be effective inhibitors of lipid peroxidation (LPx), with an almost two-fold increased inhibition of LPx compared with ascorbic acid (EC50=1.65±0.08 mg/mL), a common additive in cosmeceutical formulations and used at mg levels. Among the investigated extracts, HWCP showed the strongest inhibition potential on tyrosinase and skin extracellular matrix (ECM) degradation enzymes. These diverse functionalities indicate that G. lucidum may represent a promising source of natural cosmeceutical ingredients. https://doi.org/10.2298/ABS181217007K Received: December 17, 2018; Revised: January 30, 2019; Accepted: January 31, 2019; Published online: March 5, 2019 How to cite this article: Kozarski M, Klaus A, Jakovljević D, Todorović N, Wan-Mohtar WAAQI, Nikšić M. Ganoderma lucidumas a cosmeceutical: Antiradical potential and inhibitory effect on hyperpigmentation and skin extracellular matrix degradation enzymes. Arch Biol Sci. 2019;71(2):253-64.